Pengaruh Penerapan Akuntabilitas dan Transparansi terhadap Efektivitas Pengelolaan Dana Bantuan Operasional Sekolah (BOS) di Kota Yogyakarta - Sudyartini Sudyartini; Zaenal Wafa (Journal on Education, 2024)
This research aimed to analyze how the application of accountability and transparency principles affects the management efficiency of School Operational Assistance (BOS) funds in schools in Yogyakarta. The research population includes 80 elementary and junior high schools in Yogyakarta. The sampling technique applied was simple random sampling. For data analysis, the multiple linear regression method was used. The research results indicated that transparency and accountability positively impact the effectiveness of managing the School Operational Assistance (BOS) funds.